1D SbSeI, SbSI, and SbSBr With High Stability and Novel Properties for Microelectronic, Optoelectronic, and Thermoelectric Applications. Issue 1 (5th January 2018) - Peng, Bo; Xu, Ke; Zhang, Hao; Ning, Zeyu; Shao, Hezhu; Ni, Gang; Li, Jing; Zhu, Yongyuan; Zhu, Heyuan; Soukoulis, Costas M.
Abstract: Mechanical exfoliation of 2D materials has triggered an explosive interest in low dimensional material research. We extend this idea to 1D van der‐Waals materials. Three 1D semiconductors (SbSeI, SbSI, and SbSBr) with high stability and novel electronic properties are discovered using first principles calculations. Both the dynamical and the thermal stability of these 1D materials are examined. We demonstrate that their nanowire thinner than 7 Å can be easily obtained by mechanical exfoliation, hydrothermal method, or sonochemical method. The bulk‐to‐1D transition results in dramatic changes in band gap, effective mass, and static dielectric constant due to quantum confinement, making 1D SbSeI a highly promising channel material for transistors with gate length shorter than 1 nm. Under small uniaxial strain, these materials are transformed from indirect into direct band gap semiconductors, paving the way for optoelectronic devices and mechanical sensors. Moreover, the thermoelectric performance of these materials is significantly improved over their bulk counterparts. These highly desirable properties render SbSeI, SbSI, and SbSBr promising 1D materials for applications in future microelectronics, optoelectronics, mechanical sensors, and thermoelectrics. Abstract : 1D SbSeI, SbSI, and SbSBr with high stability and novel properties are discovered based on first principles calculations. Bulk V‐VI‐VII compounds are earth‐abundant, and isolating one chain from them can be experimentally feasible. The electronic, optoelectronic, mechanical, and thermoelectric performances are significantly improved over their bulk counterparts. A new pathway to obtain 1D nanostructures with highly desired properties is demonstrated.